Review of Islamic criminal law on decision number 81/PID/2020/PT. KPG on criminal land grabbing (stellionaat) - Alwan, Arif; Najmudin, Deden; Azazy, Yusuf (Asy-Syari’ah : Jurnal Hukum Islam, 2025)
This study will discuss about legal considerations in the ruling of Number 81/PID/2020/PT.KPG on the land usurpation and its relevance to Islamic Criminal Law. The issues that have been examined are the considerations of the judge, the elements of the jarimah, and the application of the land usurpation sentencing as viewed from Islamic perspective. The research method used a normative juridical approach with a case study and qualitative descriptive analysis. The results indicate there is a mismatch between the heaviness of the violation and the lightness of the sanctions, and the central role of the maqasid sharia values in the administration of justice. The study concludes the need for Islamic law values integration in the justice process, proposed improvements to achieve legal certainty, and the protection of the rights of society to the land through just and moral ruling. This study concludes that the ruling lacks alignment between the severity of the crime and the imposed sanction. It emphasizes the urgency of integrating Islamic criminal law values, particularly maqasid sharia, to ensure justice, legal certainty, and protection of land rights within society. Keywords: Jarimah, land, consideration